2017
DOI: 10.24248/eahrj.v1i1.388
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Aetiology, and Antimicrobial Susceptibility Patterns of Urinary Tract Infection Amongst Children Admitted at Kilimanjaro Christian Medical Centre, Moshi, Tanzania

Abstract: Background: Urinary tract infections (UTIs) in the paediatric population are well recognised as a cause of acute morbidity and chronic medical conditions, such as hypertension and renal insufficiency later in adulthood. Although antimicrobial treatment of UTIs is simple, the disease is still largely misdiagnosed and mismanaged. Moreover, increasing resistance to conventional antimicrobials is eroding the success of empiric therapy. Objective: To determine prevalence, aetiological agents, and antimicrobial sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…For example, a study from Moshi in the north-eastern part of the country identified E. coli and Klebsiella spp. as the two predominant species causing UTIs [9], while E. coli was also the major pathogen in a paediatric study from Mwanza in the northern part of Tanzania [11]. Likewise, resistance to ampicillin and cotrimoxazole was high, but only 11% of E. coli isolates displayed resistance to ciprofloxacin, which is lower than we observed in our study.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…For example, a study from Moshi in the north-eastern part of the country identified E. coli and Klebsiella spp. as the two predominant species causing UTIs [9], while E. coli was also the major pathogen in a paediatric study from Mwanza in the northern part of Tanzania [11]. Likewise, resistance to ampicillin and cotrimoxazole was high, but only 11% of E. coli isolates displayed resistance to ciprofloxacin, which is lower than we observed in our study.…”
Section: Discussioncontrasting
confidence: 77%
“…In Tanzania, only a few studies on UTIs have been conducted, and these found that UTI was a common diagnosis in 18-to 50-year-old individuals presenting to an emergency department in Ifakara [8]. Of note, rather low susceptibility rates to commonly prescribed antibiotics, such as ampicillin and cotrimoxazole, were observed [9].…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to studies performed elsewhere. 16 , 17 , 28 The higher proportion of incontinence observed in this study can be explained by the presence of a higher percentage of children aged between 2 and 4 years (53.5%) who are not bladder trained. Children with CP attain spontaneous bladder control at around 47 months of age.…”
Section: Discussionmentioning
confidence: 62%
“…Also, the observed prevalence in the current study could be influenced by the use of antibiotics at least 2 weeks before attending the rehabilitation center, due to various reasons that were reported by 18 of the respondents, The most used antibiotic was amoxicillin; this could have cleared off any organisms that could be isolated as it was observed in a previous study. 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation